2015
DOI: 10.1080/09168451.2015.1061420
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emission potentials of Burkholderia species isolated from the leaves of a boreal peat moss Sphagnum fuscum*

Abstract: Using a culture-based nitrous oxide (N2O) emission assay, three active N2O emitters were isolated from Sphagnum fuscum leaves and all identified as members of Burkholderia. These isolates showed N2O emission in the medium supplemented with [Formula: see text] but not with [Formula: see text], and Burkholderia sp. SF-E2 showed the most efficient N2O emission (0.20 μg·vial(-1)·day(-1)) at 1.0 mM KNO3. In Burkholderia sp. SF-E2, the optimum pH for N2O production was 5.0, close to that of the phyllosphere of Sphag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Another option is that bacteria growing on lichen and moss cushions are responsible for the emissions of N 2 O. This second option is supported by a recently published study, wherein several strains of the bacterial genus Burkholderia, which were shown to emit N 2 O, were isolated from the boreal peat moss Sphagnum fuscum (Nie et al, 2015). While Lenhart et al (2015) describe that the substrate, which the organisms grew on, was thoroughly removed, further cleaning steps to remove potential bacterial colonies have not been conducted.…”
Section: Introductionmentioning
confidence: 89%
“…Another option is that bacteria growing on lichen and moss cushions are responsible for the emissions of N 2 O. This second option is supported by a recently published study, wherein several strains of the bacterial genus Burkholderia, which were shown to emit N 2 O, were isolated from the boreal peat moss Sphagnum fuscum (Nie et al, 2015). While Lenhart et al (2015) describe that the substrate, which the organisms grew on, was thoroughly removed, further cleaning steps to remove potential bacterial colonies have not been conducted.…”
Section: Introductionmentioning
confidence: 89%
“…Isolates from Sphagnum mosses that cover a Finnish acidic mire included isolates from Burkholderia sp. that have their optimum pH at around 5 and emit N 2 O, when NO 3 − was supplemented during incubation (Nie et al, 2015). All isolates possessed the narG gene for nitrate reduction, but amplification of either typical or atypical nosZ gene was not successful, suggesting these Burkholderia sp.…”
Section: Otu1mentioning
confidence: 99%
“…Winograsky's mineral solution containing 0.5% (w/v) sucrose and 5 mM KNO 3 (0.52 g L -1 ) was used as the medium in the culture-based N 2 O reduction assay (Hara et al, 2009;Nie et al, 2015). Since pH plays a key role in the emission of N 2 O (Nie et al, 2015), the pH of the solution was adjusted to various values (4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, and 9.0) using 2 M H 2 SO 4 and 1 M KOH that was gelled with 0.5% (w/v) gellan gum and then autoclaved. The same medium was used in subsequent experiments.…”
mentioning
confidence: 99%
“…The same medium was used in subsequent experiments. N 2 O levels were measured as described in a previous study (Nie et al, 2015). N 2 O was emitted in the culture at pH 4.5-7.5 ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation